Is individual day-to-day variation of arterial stiffness associated with variation of maximal aerobic performance? - Okamoto, T.; Kobayashi, R.; Hashimoto, Y.; Kikuchi, N.; Ogoh, S. (BMC Sports Science, Medicine and Rehabilitation, 2021)
Maximal aerobic capacity, e.g. maximal oxygen uptake (V.O2max), is not constant, and it has a time-dependent variation based on the condition of individual. On the other hand, arterial properties play an important role in determining aerobic performance, and lower arterial stiffness is associated with higher cardiorespiratory fitness levels. This study examined whether individual variations in maximal aerobic performance are associated with arterial stiffness. Methods